Laporan Kasus: Mioma Uteri pada Pasien Perempuan Usia 41 Tahun - Khairun Nisa; Iskandar Albin (Lembaga Pengembangan Kinerja Dosen, 2026)
Uterine myoma is a benign smooth muscle tumor of the uterus commonly found in women of reproductive age and may cause symptoms related to mass effect and hematologic disturbances. We report the case of a 41-year-old woman presenting with progressive vaginal pain for 3 months, accompanied by low back pain and impaired daily activities, without vaginal bleeding, vaginal discharge, fever, or urinary or defecatory symptoms. Laboratory examination revealed severe microcytic hypochromic anemia with a hemoglobin level of 4.7 g/dL, while ultrasonography demonstrated a 9.93 × 10.32 cm mass described as symmetric, well circumscribed, and hyperechoic, leading to a working diagnosis of uterine myoma with anemia. The patient was managed with general condition monitoring, intravenous fluids, analgesics, transfusion of four units of packed red cells, and laparotomy as definitive intervention. Following transfusion and surgery, the hemoglobin level increased to 9.4 g/dL and subsequently to 11.0 g/dL, accompanied by improvement in postoperative symptoms and clinical condition. This case demonstrates that a large uterine myoma may present predominantly with pelvic pain and functional impairment in the absence of vaginal bleeding. A comprehensive approach involving systematic evaluation, preoperative correction of anemia, appropriate surgical intervention, and postoperative monitoring is essential to improve safety and clinical outcomes in patients with symptomatic pelvic masses.